Pre-clinical evaluation of cysteamine bitartrate as a therapeutic agent for mitochondrial respiratory chain disease - Guha, Sujay (Hum Mol Genet, 2019)
Cysteamine bitartrate is a US Food and Drug Administration-approved therapy for nephropathic cystinosis also postulated to enhance glutathione biosynthesis. We hypothesized this antioxidant effect may reduce oxidative stress in primary mitochondrial respiratory chain (RC) disease, improving cellular viability and organismal health. Here, we systematically evaluated the therapeutic potential of cysteamine bitartrate in RC disease models spanning three evolutionarily distinct species. These pre-clinical studies demonstrated the narrow therapeutic window of cysteamine bitartrate, with toxicity at millimolar levels directly correlating with marked induction of hydrogen peroxide production. Micromolar range cysteamine bitartrate treatment in Caenorhabditis elegans gas-1(fc21) RC complex I (NDUFS2(−/−)) disease invertebrate worms significantly improved mitochondrial membrane potential and oxidative stress, with corresponding modest improvement in fecundity but not lifespan. At 10 to 100 μm concentrations, cysteamine bitartrate improved multiple RC complex disease FBXL4 human fibroblast survival, and protected both complex I (rotenone) and complex IV (azide) Danio rerio vertebrate zebrafish disease models from brain death. Mechanistic profiling of cysteamine bitartrate effects showed it increases aspartate levels and flux, without increasing total glutathione levels. Transcriptional normalization of broadly dysregulated intermediary metabolic, glutathione, cell defense, DNA, and immune pathways was greater in RC disease human cells than in C. elegans, with similar rescue in both models of downregulated ribosomal and proteasomal pathway expression. Overall, these data suggest cysteamine bitartrate may hold therapeutic potential in RC disease, although not through obvious modulation of total glutathione levels. Careful consideration is required to determine safe and effective cysteamine bitartrate concentrations to further evaluate in clinical trials of human subjects with primary mitochondrial RC disease.